Unspoken Therapy: Dogs’ Contribution to Their Owners’ Well-being, Coping Mechanism, and Newfound Meaning in Life - Daisy T. Kazandjiev; Sharon Rose G. Medez (Philippine Social Science Journal, 2025)
Addressing the mental and emotional challenges of solitary living, this qualitative phenomenological study explores the therapeutic impact of dog ownership on well-being. Through unstructured interviews with empty nesters and childless couples, analyzed via Lichtman’s 3Cs, the research reveals that dogs function as vital companions—or "four-legged therapists"—that facilitate coping, resilience, and a renewed sense of purpose. These findings underscore the profound value of the human-animal bond, validating the implementation of dog-assisted therapy programs in academic, clinical, and corporate settings. Ultimately, this study establishes a foundation for future quantitative research to expand these interventions to broader populations, including students and the workforce, to further substantiate the role of dogs in mental healthcare.